2020
DOI: 10.1038/s43016-020-0045-6
|View full text |Cite
|
Sign up to set email alerts
|

The hidden potential of urban horticulture

Abstract: ood insecurity is a growing issue in the Global North 1,2 , where the majority of the population (sometimes in excess of 80%) lives in urban areas 3. Food production in urban areas, particularly horticultural production 4,5 , is increasingly recognized at all levels of governance, from local to transnational, as an important contributor to food security 6. Despite this recognition, there have been few attempts to analyse the feasibility of urban horticulture (UH) in terms of the space available within the urba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 27 publications
0
53
0
Order By: Relevance
“…To meet the food demands of an urban population, land in and round the cities, such as green belts, land adjacent to sidewalks, vacant plots, community gardens, botanical gardens, and rooftops should be used efficiently. A recent case study from Sheffield, UK, showed that there are large potential spaces available to produce more than enough fruits and vegetables to fulfill the needs of urban inhabitants [67]. Cleveland, Ohio, a city of 400,000 inhabitants, has the potential to fulfill resident demands by growing fresh vegetables on rooftops and conducting vertical gardening in vacant spaces [68].…”
Section: Self-reliance and Land Management Of Citiesmentioning
confidence: 99%
“…To meet the food demands of an urban population, land in and round the cities, such as green belts, land adjacent to sidewalks, vacant plots, community gardens, botanical gardens, and rooftops should be used efficiently. A recent case study from Sheffield, UK, showed that there are large potential spaces available to produce more than enough fruits and vegetables to fulfill the needs of urban inhabitants [67]. Cleveland, Ohio, a city of 400,000 inhabitants, has the potential to fulfill resident demands by growing fresh vegetables on rooftops and conducting vertical gardening in vacant spaces [68].…”
Section: Self-reliance and Land Management Of Citiesmentioning
confidence: 99%
“…More broadly, the pursuit of urban agriculture has benefits in the production of food closer to points of demand, reducing monetary and environmental transport costs and making greater use of local resources that may otherwise be treated as waste, such as rain runoff (Al-Kodmany 2018). Urban agriculture faces many challenges to adoption, and its greatest introduced risks stem from uncertainties around its unexplored economics; however, the importance of its untapped potential is being increasingly recognised (Edmondson et al 2020;Grafius et al 2020). The opportunities in this case are geographical and integrative, and the main ecological principle is cyclical flow.…”
Section: Case Study: Circular Resource Model For Urban Agriculturementioning
confidence: 99%
“…Australian and US community gardens and UK allotments are regularly established in communities of low socio-economic status, and often on parcels of ‘waste’ land that are reclaimed for food production. Some UK researchers argue that small scale allotments can grow sufficient produce to meet daily fruit and vegetable consumption requirements [ 48 ]. More recently, community gardening has been recognized as important in mitigating the impacts of climate change [ 49 ] and enhancing biodiversity [ 50 ].…”
Section: The Role and Function Of Campus Community Gardensmentioning
confidence: 99%